2009
DOI: 10.1111/j.1601-183x.2008.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in COMT and neurocognitive impairment in families of patients with schizophrenia

Abstract: This study examined the relations of genetic variants in catechol-O-methyltransferase (COMT) gene, including rs737865 in intron 1, rs4680 in exon 4 (Val158Met) and downstream rs165599, to schizophrenia and its related neurocognitive functions in families of patients with schizophrenia. Totally, 680 individuals from 166 simplex (166 affected members and 354 nonpsychotic firstdegree relatives) and 46 multiplex families (85 affected members and 75 nonpsychotic first-degree relatives) were interviewed using Diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 59 publications
1
11
0
1
Order By: Relevance
“…Hence the results should be interpreted with caution. In the same vein, a marginal association with rs4680, an exonic SNP at COMT was noted in our case-control sample and has also been reported by several other investigators (Handoko et al., 2005;Nunokawa et al, 2010;Liao et al, 2009; Okochi et al, 2009; Bhakta et al, 2012; Singh et al., 2012). Apart from these exonic variants, nominally significant SNP associations were also noted at all the other genes tested, except at SLC6A3 (Table I) in either case-control or family based analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Hence the results should be interpreted with caution. In the same vein, a marginal association with rs4680, an exonic SNP at COMT was noted in our case-control sample and has also been reported by several other investigators (Handoko et al., 2005;Nunokawa et al, 2010;Liao et al, 2009; Okochi et al, 2009; Bhakta et al, 2012; Singh et al., 2012). Apart from these exonic variants, nominally significant SNP associations were also noted at all the other genes tested, except at SLC6A3 (Table I) in either case-control or family based analysis.…”
Section: Discussionsupporting
confidence: 92%
“…There is limited research investigating the influence of COMT val 108/158 met polymorphism on CPT performance and thus far, the findings have been mixed (Caldú et al, 2007; Eisenberg et al, 1999; Liao et al, 2009; MacDonald, Carter, Flory, Ferrell, & Manuck, 2007; Mills et al, 2004). Importantly, the exact nature of the role of COMT in cognitive function is unclear with regard to specificity.…”
Section: Introductionmentioning
confidence: 99%
“…73,251 Furthermore, this polymorphism has frequently been associated with WSCT performance, although recent studies and a meta-analysis have found that the association may only be small, although significant. 252,253 Finally, mutations in COMT have also been associated with social anhedonia. 254 In animal model studies, male homozygous Comt knockout mice showed a 2-to 3-fold increase in DA levels, although female mice did not.…”
Section: Catechol-o-methyltransferase (Comt)mentioning
confidence: 99%